Role of galectin 3 and thyroid peroxidase as diagnostic tool in thyroid carcinoma with clinicopathological correlation: a cohort study of 94 cases - Verma, Nidhi; Singh, Neha; Gupta, Priya; Singh, Preeti; Sagar, Harish Kumar (International Journal of Research in Medical Sciences, 2022)
Background: Thyroid neoplasms constitute the most commonly occurring endocrine tumors worldwide. With ultrasonography, detection has been increased up to 30%. Thyroid neoplasms have a wide spectrum of clinical behaviour and varied therapeutic responsiveness. Thus, early diagnosis of thyroid tumors and appropriate management will prolong the survival rate of patients. So, this study focuses on thyroid tumors which have overlapping morphological features and exact diagnosis is essential for surgical and post- operative management of patients. The aim and objective of the study was to determine the role of Galectin 3 and Thyroid Peroxidase in malignant tumors of thyroid as diagnostic marker. Methods: We evaluated the patients for detailed history, physical examination, fine needle aspiration cytology (FNAC) and biopsy or excision of thyroid gland and subsequently histological examination and Immunohistochemistry for galectin 3 and thyroid peroxidase antibody (TPO). Results: A total of 94 cases were enrolled in the study. Out of these 94 cases, 70 cases (74%) were followed by histopathology and immunohistochemistry (IHC). Out of 70 cases, benign were 44 (63%) and malignant were 26 (37%). Among benign cases, most common were colloid goitre, 22 cases (31%). Among malignant cases, most common were papillary carcinoma, 15 cases (21%). For all thyroid carcinoma, both Galectin 3 and TPO showed sensitivity of 81% when used alone. However combination of galectin 3 and TPO increased the sensitivity up to 92%. Conclusions: Galectin 3 and TPO alone has high sensitivity for all thyroid carcinoma but sensitivity was markedly increased when combination of the two markers were used.